If x= 3 is one of the quadratic equation x^2 - 2 kx - 6 = 0, then find the value of k.
Answers
Answered by
0
her dear your answer is in the attachment
Attachments:
![](https://hi-static.z-dn.net/files/d3a/ae2390c66bf7fa676b53613368daea53.jpg)
![](https://hi-static.z-dn.net/files/d9c/2239b69cd9af6c5c4f7d27fa781707e9.jpg)
Apxex:
Sorry I added new attachment a clear one
Answered by
1
thus,
Substituting x=3 in the quadratic equation,
[tex] x^{2} -2kx-6=0 3^{2} -2k(3)-6=0 9-6k-6=0 3(3-2k-2)=0 Dividing both sides by 3 3-2k-2=0 1-2k=0 1=2k 1/2=k thus k=1/2 [/tex]
Substituting x=3 in the quadratic equation,
[tex] x^{2} -2kx-6=0 3^{2} -2k(3)-6=0 9-6k-6=0 3(3-2k-2)=0 Dividing both sides by 3 3-2k-2=0 1-2k=0 1=2k 1/2=k thus k=1/2 [/tex]
Similar questions